Women and consent to unwanted marriage in Middle English romance and antecedent discourses - Cable, Felicity Rosalind (Trinity College (Dublin, Ireland). School of English, 2008)
This dissertation addresses female resistance to marriage in popular Middle English romance. It presents a thematic study encompassing the history and transmission of misogamy in the Middle Ages, tracing the anti-matrimonial disposition to the exegesis of the early Christian Fathers whose tendentious use of Pauline epistles influenced subsequent generations of scholars and elective single women. The dissertation makes extensive use of manuscript and printed sources; in addition to the close reading of courtship and nuptial description in the texts of some thirty late medieval English romances and their French or Anglo-Norman antecedents, I draw on contextual works of clerical and lay authorship. These include the patristic writings, decrees of medieval canon lawyers, variant versions of the hagiographic literature of two specimen virgin martyrs, courtesy books, civic ordinances, court depositions, testaments and private correspondence. In an attempt to avoid the elitist assumptions of literary sources and bibliographic scholarship, 1 also examine the widespread dissemination of marital and anti-marital messages in the visual media, predominantly in the public domain.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin